Postpartum Pyomyoma, a Rare Complication of Sepsis Associated with Chorioamnionitis and Massive Postpartum Haemorrhage Treated with an Intrauterine Balloon - Mandeep Kaler; Ruth Gailer; Joseph Iskaros; Anna L. David (Hindawi Limited, 2015)
We report the successful treatment of a postpartum pyomyoma, a rare but serious complication of uterine leiomyomata in a 28-year-old primigravida. The patient was treated for an Escherichia Coli (E. Coli) urinary tract infection (UTI) at 16 weeks of gestation. She had asymptomatic short cervical length on ultrasound scan at 20 weeks that was managed conservatively due to the presence of further UTI and received antibiotics. She was known to have a left sided intramural leiomyoma. She presented with abdominal pain and vaginal bleeding at 23+1 weeks of gestation and the next day she had spontaneous vaginal delivery and collapsed with E. Coli septic shock, massive postpartum haemorrhage, and disseminated intravascular coagulation and was successfully treated with oxytocic drugs, a Rusch intrauterine balloon, and intravenous antibiotics. Eleven days postnatally she re-presented with systemic sepsis and was treated for retained products of conception. Sepsis persisted and investigations showed a postpartum pyomyoma that was initially managed with intravenous antibiotics to avoid surgery. Ultimately she required laparotomy, drainage of pyomyoma, and myomectomy. Postoperative recovery was good and the patient had a successful pregnancy two years later.